Physico-Chemical Characteristics of Soil And Fly-Ash Around Chandrapura Thermal Power Station: A Comparison - Siddarth Singh, B. K.Tewary, Dadhibal Prasad Gond, Amit Pal, (Journal of Phytology, 2009)
Abstract : Fly-ash and native material (soil) were evaluated for physico-chemical properties and trace elements in their lechates as an essential requirement for environmentally safe disposal and improvement for soil fertility. Fly-ash and soil samples were randomly collected from Chandrapura Thermal Power Station (Bokaro, Jharkhand, India) and brought to Central Institute of Mining and Fuel Research, Dhanbad. Fly-ash and soil samples were leached with deionized water and lechates were analyzed following the methodology by ASTM (American Society for Testing Material) to determine the pH, EC, Ca, Mg, OC, Om, P and K. The extract of DTPA for micronutrients was determined.